Induced Mutation for Genetic Improvement in Black Rice Using Gamma-Ray - Edi Purwanto; Nandariyah Nandariyah; Suhadi Sapto Yuwono; Mercy Bientri Yunindanova (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2019)
Black Rice is rice producing anthocyanin in high intensity and popularly consumed as functional food. Long harvesting age and low productivity are the inhibiting factors in black rice breeding. High plant crown potentially results in plant fall-down. Mutation induction is expected to be able to improve the character of black rice. Therefore, the objectives of this research were to get more early-ripening black rice mutant, with shorter plant crown and increase productivity by inducing mutation in three varieties of local black rice using gamma-ray radiation. This experiment employed three local varieties as the first factor comprised Cempo Ireng, Cempo Melik and Melik. The second factor was the gamma-ray radiation dose, consisting of 4 levels: without radiation, radiations at 100 Gy, 200 Gy and 300 Gy doses. The results indicated that Melik variety is very potential. Melik variety has shorter plant crown with a responsive character in number of tiller for higher productivity. Moreover, radiation significantly reduces the duration of flowering and harvesting. However, to achieve a more stable character and lower flowering and harvesting period, the radiation needs to be continued in the next generation. The doses of radiation produces a response that varies in both morphological and biochemical properties.